2021
DOI: 10.1007/s00395-021-00902-7
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-free tumor elimination in mice leads to functional and molecular cardiac recovery from cancer-induced alterations in contrast to long-lasting doxorubicin treatment effects

Abstract: Systemic effects of advanced cancer impact on the heart leading to cardiac atrophy and functional impairment. Using a murine melanoma cancer model (B16F10 melanoma cells stably transduced with a Ganciclovir (GCV)-inducible suicide gene), the present study analysed the recovery potential of cancer-induced cardiomyopathy with or without use of doxorubicin (Dox). After Dox-free tumor elimination and recovery for 70 ± 5 days, cancer-induced morphologic, functional, metabolic and molecular changes were largely reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
(73 reference statements)
0
7
2
Order By: Relevance
“…Thus, the heart is not able to recover from leukemia-induced cardiac damage and harbors long-lasting cardiac side effects under these conditions. In contrast to our data, a recently published study has demonstrated that a reversible murine cancer model using B16F10 melanoma-HSV-TK cells enabling melanoma-cell-specific chemotherapy-free elimination by GCV treatment showed cardiac recovery [ 46 ]. In addition, after cardiac recovery, all melanoma-induced phenotypic, metabolic, molecular and functional changes in the heart were almost reversible after GCV-mediated tumor elimination without evidence of a contribution to long-term cardiac damage [ 46 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, the heart is not able to recover from leukemia-induced cardiac damage and harbors long-lasting cardiac side effects under these conditions. In contrast to our data, a recently published study has demonstrated that a reversible murine cancer model using B16F10 melanoma-HSV-TK cells enabling melanoma-cell-specific chemotherapy-free elimination by GCV treatment showed cardiac recovery [ 46 ]. In addition, after cardiac recovery, all melanoma-induced phenotypic, metabolic, molecular and functional changes in the heart were almost reversible after GCV-mediated tumor elimination without evidence of a contribution to long-term cardiac damage [ 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our data, a recently published study has demonstrated that a reversible murine cancer model using B16F10 melanoma-HSV-TK cells enabling melanoma-cell-specific chemotherapy-free elimination by GCV treatment showed cardiac recovery [ 46 ]. In addition, after cardiac recovery, all melanoma-induced phenotypic, metabolic, molecular and functional changes in the heart were almost reversible after GCV-mediated tumor elimination without evidence of a contribution to long-term cardiac damage [ 46 ]. These data clearly demonstrate that, depending on the type of cancer, different strong and long-lasting cardiac complications and adverse effects may occur.…”
Section: Discussioncontrasting
confidence: 99%
“…Doxorubicin is one of the most classical chemotherapeutics and has been extensively used for cancer therapy ( 3 , 4 ). However, drug resistance and serious side effects limited its further clinical application ( 5 , 6 ). Therefore, developing new therapeutic drugs that can effectively treat colon cancer is urgent and essential.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer patients, cachexia with potential adverse consequences for cardiac integrity affects up to 74% of cancer patients, with significant consequences on long-term cardiovascular health [3]. Understanding the underlying pathomechanisms and their implications on acute and late cardiac dysfunction is crucial to optimize the management of cardio-oncology patients [6,15,18,23].…”
mentioning
confidence: 99%
“…In this issue of Basic Research in Cardiology, Pietzsch and colleagues shed new light on the often neglected impact of the underlying cancer on the recovery after cancer-induced cardiomyopathy [ 16 ]. As a novel approach, the authors establish a reversible melanoma mouse model on the basis of the common B16F10 melanoma cell line that was genetically modified via lentiviral transduction of a suicide gene that could induce cell death upon exposure to ganciclovir.…”
mentioning
confidence: 99%